2023
DOI: 10.1101/2023.02.26.529821
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural homology screens reveal poxvirus-encoded proteins impacting inflammasome-mediated defenses

Abstract: Viruses acquire host genes via horizontal gene transfer and can express them to manipulate host biology during infections. Some viral and host homologs retain sequence identity, but evolutionary divergence can obscure host origins. We used structural modeling to compare vaccinia virus proteins with metazoan proteomes. We identified vaccinia A47L as a homolog of gasdermins, the executioners of pyroptosis. An X-ray crystal structure of A47 confirmed this homology and cell-based assays revealed that A47 inhibits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…First, we found that a set of proteins encoded by poxviruses are structurally similar to the auto-inhibitory domain of mammalian gasdermins (Fig. 3D) 32 . Similarly, several poxvirus proteins are structurally homologous to the human galactosyltransferase COLGALT1, thought to enable virus binding to surface glycosaminoglycans during viral entry (Fig.…”
Section: Structural Alignments Suggest Functions Of Human Pathogen Pr...mentioning
confidence: 92%
“…First, we found that a set of proteins encoded by poxviruses are structurally similar to the auto-inhibitory domain of mammalian gasdermins (Fig. 3D) 32 . Similarly, several poxvirus proteins are structurally homologous to the human galactosyltransferase COLGALT1, thought to enable virus binding to surface glycosaminoglycans during viral entry (Fig.…”
Section: Structural Alignments Suggest Functions Of Human Pathogen Pr...mentioning
confidence: 92%
“…Protein B14 blocks NF-κB activation by binding to IKKβ and thereby prevents phosphorylation of IκBα [ 15 ]. Protein C1 is not anti-apoptotic [ 16 ] but promotes inflammasome activation [ 17 ]. Protein C6 is a multifunctional IFN antagonist that inhibits IRF3 activation in 2 ways.…”
Section: Introductionmentioning
confidence: 99%